Liability of Legal Persons for Criminal Offenses Against the Environment (Experiences of the Republic of Croatia) - Mladinić, Nina; Sokanović, Lucija; Kurtović Mišić, Anita (Glasnik Advokatske komore Vojvodine, 2025)
For twenty years, the Republic of Croatia has recognized the liability of legal entities for all criminal offenses contained in the Criminal Code, including criminal offenses against the environment. Along with the existence of awareness of the danger of organized environmental crime, the issue of punishability of legal persons and the prosecution for criminal association in criminal organizations are regulated in an appropriate normative manner, and the environment is adequately protected by special criminal offenses. The environment is primarily protected by non-punitive mechanisms of other legal branches, which accepted the combined model of administrative, misdemeanor, and criminal sanctions. Statistical data show that the number of convicted legal persons for environmental crime in the Republic of Croatia is negligible, and the aim of the paper was to investigate the issue of applying the legal regulation of corporate responsibility for environmental crime by presenting statistical data and analyzing individual cases. The purpose of the conducted research is to answer the question of whether there is a gap between normative solutions and their application in case law, and what problems arise when reporting, prosecuting, and convicting legal entities as perpetrators of criminal offenses against the environment.
Keywords: legal persons; criminal liability; environmental crime; organized crime; Law on the Liability of Legal Persons for Criminal Offenses; criminal prosecution